Microstructure, Mechanical, and Electrical Properties and Corrosion Analysis of Lead-Free Solder CSI Joints on Cu Substrate Using Novel Concentrated Solar Energy Soldering (CSES) Method - Pushkaraj D. Sonawane; V. K. Bupesh Raja; Manoj Gupta (Advances in Materials Science and Engineering)
In this study, “Concentrated Solar Energy (CSE)” is applied for soldering and is named as the “Concentrated Solar Energy Soldering (CSES) technique.” Lead-free solders are used for comparing novel CSES technique solder joints with CSI (Conventional Soldering Iron) solder joints. Tensile strength, bending/flexural strength, microhardness, electrical resistivity, fractography, optical microstructures, SEM microstructures, and EDS analysis were used to compare CSES solder joints with CSI solder joints. The salt spray test (SST) was used for corrosion analysis of CSES and CSI solder joints. Experimental results reveal that the tensile response, bending strength, and microhardness of the CSES solder joints were almost equal to those of the CSI solder joints. It was observed that after corrosion, the tensile strength, bending strength, and microhardness for CSES and CSI solder joints reduced. CSES solder joints were found to be slightly better than CSI solder joints for electrical resistivity. Electrical resistivity for all the cases studied was found to increase slightly after corrosion. Interfacial integrity and effect of corrosion were clearly observed on CSES and CSI solder joint microstructures. The intermetallic compounds (IMC) formed in case of CSES solder joints were found to be having slightly less thickness than that of CSI solder joints. The results demonstrate CSES technique as a green technology and a potential substitute to the CSI method.